Resources EE job market brightens. - Costlow, T. (IEEE spectrum)
Some experts observe that the engineering job market is coming back from the depths of technical wreck, particularly in certain areas. But they also observe that even though hiring may be up, the climb starts from a low point. The experts also forecast an increase in employment. But even as employers add staff, they are being extra cautious, thoroughly vetting job applicants before making an offer. This paper discusses the present state of the engineering job market.